Pest complex associated with mango inflorescence and their control - Satheesan N V (Department of Agricultural Entomology, College of Horticulture, 1984)
In a survey conducted during 1982-83 in the State of Kerala to study the incidence of various insect pests associated with mango inflorescence with reference to their seasonal history, a total of ten insect pests were recorded. The hoppers idioscopus niveosparaus Leth. and I. clypealis Leth. were found to be widely distributed in the State. Significant variability was not detected among the population loads of I. niveosparsus in different districts, while in the case of I. clypealis such variations were significant. The heaviest populations of the latter was recorded from the Calicut District. The seasonal changes in I. clypealis populations were recorded only in the two Districts of Calicut and Trivandrum. I. niveosparsus showed a well defined peaks in the Palghat and Wynad districts. The fluctuations I. niveosparsus and I. clypealis populations have been discussed with reference environmental conditions. Procystiphora mangiferae Felt. is reported for the first time from the State from the Wynad and Cannanore Districts. Infestations by the pest led to transformation of the floral buds to conical galls. In the Wynad District, there was a well defind population peak in March, while in the Cannanore District a district crest waslacking. The mango blister midge, Erosomyia indica grover and Prasad was recorded to occur in association with P. mangiferae in these two districts. The larvae of E. indica tunnel into inflorescence axis and cause ovate galls thereby causing losses. Bombotelia jocosatrix Gn. was recorded from the Cannanore, Palghat, Trichur and Alleppey Districts throughout the flowering season. Eublemma anguilifera Moore as well as another unidentified spp. of Eublemma were recorded to occur throughout the State, except in the wynad District. The seasonal fluctuations of this pest were significant only in the Palghat District. An unidentified species of Cacoecia was recorded for the first time as a minor pest of mango inflorescence. The larvae fed on flowers and floral buds. The other pests observed during the course of the survey were Rapala manea Hewitson, Haplothrips ganglbaueri Schmutz, Dichocrosis punctiferalis Guenee and an unidentified Geometrid. The bio-efficiency of monocrotophos applied by two methods, namely, stem injection and stem banding, against the Idiocerine hoppers infesting mango inflorescence was evaluated in a separate experiment. The relative toxicity of the insecticide was determined from the time- mortality relationship between the insecticide reaching the inflorescence of treated trees and the mortality of the fourth instar nymphs of I. niveosparsus. The LT -50 values of the nymphs following application of the insecticides by the stem injection method was found to be substantially lower than the corresponding values for the stem banding method of application. It was thus evident that the toxicant moved at a faster pace when administered by the stem injection method. The variations in the pattern of translocation of the toxicant under the two methods of administration have been discussed. The residues of monocrotophos on freshly formed mango fruit at five weeks after application by the stem injection method at 4 ml and 2 ml ai/tree were 0.3600 ppm and o.3750 ppm respectively. The corresponding residues in the mango fruit consequent on stem banding method of administration were 0.0550 ppm. The implications of the above results in formulating control methods against Idiocerine hoppers infesting mango inflorescence have been discussed.